PENYEBAB PENUNDAAN PERNIKAHAN PADA KALANGAN MILENIAL ANALISIS MASLAHAH MURSALAH - M. Habib Fadhila; Eko Hidayat; Ahmad Burhanudin (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This study examines marriage delay among Millennials in Bandar Lampung City through the lens of maslahah mursalah. Globalization fosters individualistic values, prioritizing career, financial independence, and personal achievement, alongside economic pressures like high living costs, inflation, and post-pandemic uncertainty. Statistics Indonesia (BPS) data reveals rising average marriage ages, clashing with Islamic sunnah's goals of tranquility (sakinah) and pious offspring.Employing qualitative methods interviews, observations, and Miles-Huberman analysis the research identifies marriage delay as potential maslahah hajiyyah, safeguarding family well-being (hifẓ al-māl) and rational self-determination (hifẓ al-‘aql), provided it remains moderate and avoids endangering lineage preservation (hifẓ an-nasl). Prolonged delays, however, risk harms like declining birth rates and loneliness. The study concludes a tension between Islamic teachings and modern realities demanding holistic readiness. Maslahah mursalah resolves this by balancing jalb al-maṣāliḥ (benefits of independence) and dar’ al-mafāsid (averting long-term harms). This contributes to contemporary ijtihad in Indonesia, reinforcing marriage as a sacred, peaceful institution amid globalization's dynamics.